INTEGRATING MONTESSORI, NEUROSCIENCE, AND ISLAMIC VALUES IN EARLY SCIENCE AND MATH LEARNING: - - Yuniarti, Nita; Suyadi (PG PAUD Universitas Negeri Surabaya, 2025)
This paper aims to analyze and integrate the Montessori approach and neuroscience in early childhood science and mathematics education with Islamic values. One of the main challenges of early childhood education in Indonesia is the low interest in science and mathematics, which are often perceived as abstract and difficult, reflected in the country’s relatively low global ranking. Neuroscience emphasizes that early childhood represents a golden age to optimize children’s potential for logical, critical, and exploratory thinking. The Montessori method, which is grounded in concrete experiences and multisensory stimulation, can help children construct abstract concepts through real-life activities (tarbiyah bil hal). Integration with Islamic values further enriches the spiritual dimension, guided by the Qur’anic encouragement for humans to yatafakkar (reflect), yatadabbar (contemplate), ta’ammul (engage in deep reflection), and yansur (observe/investigate) the order of Allah’s creation. Moreover, this approach highlights the importance of education through lived example, so that children learn not only with their intellect, but also with their hearts and behavior. This study employs a descriptive literature review by analyzing both classical and contemporary sources on Montessori, neuroscience, and Islamic education. The findings indicate that a Montessori–Neuroscience–Islam integrated model in science and mathematics education not only stimulates cognitive development, but also nurtures children’s spiritual awareness, thus offering a holistic, integrative, and contextually relevant alternative for early childhood education in Indonesia.